2023
DOI: 10.1007/s10654-022-00960-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimates and Forecasts on the Burden of Prediabetes and Diabetes in Adult and Elderly Population in Turkiye

Abstract: Aims Diabetes mellitus is a chronic disease that limits the quality and duration of life. We aimed to estimate the impact of demographic change on the burden of prediabetes and diabetes between 2010 and 2021, and the projections to 2030 and 2045 in Turkiye. Materials and methods Prediabetes and diabetes estimates were calculated by direct standardization method using age- and sex-specific prevalence data from the previous ‘Turkish Epidemiology Survey of Diabetes, Hypert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…[1335]. В турецком исследовании "Turkish Epi demiology Survey of Diabetes, Hypertension, Obesity and Endocrine Disease" (TURDEP-II) продемонстрировано общее увеличение лиц с предиабетом с 7 млн человек до 8,5 млн (по глюкозе крови натощак) [1336].…”
Section: предиабет сахарный диабет и коморбидность 421 предиабет и ко...unclassified
“…[1335]. В турецком исследовании "Turkish Epi demiology Survey of Diabetes, Hypertension, Obesity and Endocrine Disease" (TURDEP-II) продемонстрировано общее увеличение лиц с предиабетом с 7 млн человек до 8,5 млн (по глюкозе крови натощак) [1336].…”
Section: предиабет сахарный диабет и коморбидность 421 предиабет и ко...unclassified
“…More and more evidences have suggested that diabetes is a multifactorial disease accompanied by the dysregulation of lipid and glucose metabolism, and oxidative stress, which plays an important role in the occurrence and development of diabetes ( Maria and Mattias, 2017 ; Hu et al, 2020 ; Sourbh and Jeena, 2022 ). The long-term hyperglycemia in patients with diabetes may lead to chronic injury and dysfunction of various tissues ( Satman et al, 2023 ; Min et al, 2024 ). Although the commonly used hypoglycemic clinical agents, such as metformin and glibenclamide can lower blood glucose, they often induce a range of side effects including diarrhea, intestinal flatulence, hemolytic anemia, lactic acidosis and congestive heart failure ( Xing et al, 2021 ; Elkhalifa et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% to 30% of the elderly population is estimated to have diabetes, although the numbers vary among countries [ 1 - 3 ]. Elderly patients with diabetes commonly have other medical conditions (e.g., cardiovascular disease, chronic kidney disease, or heart failure [HF]) and are at an increased risk of mortality, which may impose a substantial socioeconomic burden on society [ 4 - 6 ]. Furthermore, accumulating evidence indicates that mortality trends in patients with diabetes are changing [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%